Implementation of The Hope Family Program (PKH) in Bligo Village, Candi District, Sidoarjo Regency - Ningrum, Retno Agustin; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the implementation of the Family Hope Program (PKH) in Bligo Village, Candi District, Sidoarjo Regency and to determine the supporting factors and inhibiting factors for the implementation of the Expected Family Program. This study uses a qualitative descriptive research method with the technique of determining the informant using purposive sampling. The location of this research is in Bligo Village, Candi District, Sidoarjo Regency. Data collection techniques obtained by means of observation, documentation and interviews. The collection technique consists of data collection, data reduction, data presentation and conclusion drawing. The method used for research is the method according to Edward III and has 4 factors consisting of communication, resources, disposition and bureaucratic structure. The results of this study indicate that the implementation of the Family Hope Program in Bligo Village, Candi District, Sidoarjo Regency in terms of communication is still not optimal, in terms of resources, it is in accordance with the job disk and the facilities provided are appropriate, in terms of disposition, implementation is in accordance with regulations and has commitment. and in terms of bureaucratic structure has been implemented. Constraints faced from data inhibiting factors which are still top-down and supporting factors for very high public enthusiasm